2016
DOI: 10.1177/0081246316654804
|View full text |Cite
|
Sign up to set email alerts
|

The impact of a career intervention programme on South African Grade 11 learners’ career decision-making self-efficacy

Abstract: There have been increasing calls for career development interventions that take the local context into account while providing a firm theoretical basis to engage with the career processes and attributes of individuals coming from diverse backgrounds. The goal of this study was to determine the effect of a career intervention programme derived from Social Cognitive Career Theory on the career decision-making self-efficacy of Grade 11 learners at three schools with diverse socio-economic backgrounds in the Easte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 33 publications
0
12
0
Order By: Relevance
“…This finding reinforces the evidence base that interventions incorporating Bandura’s four sources of information through which self-efficacy is modified are indeed effective in modifying CDSE (Reese & Miller, 2006; Scott & Ciani, 2008). This study not only builds on the work of Miles and Naidoo (2016), who found gains in CDSE following the completion of careers intervention program based on Bandura’s four sources of information and Brown and Crane’s five critical ingredients, but goes one step further by demonstrating that such interventions can be effective in reducing CDDs.…”
Section: Discussionmentioning
confidence: 90%
“…This finding reinforces the evidence base that interventions incorporating Bandura’s four sources of information through which self-efficacy is modified are indeed effective in modifying CDSE (Reese & Miller, 2006; Scott & Ciani, 2008). This study not only builds on the work of Miles and Naidoo (2016), who found gains in CDSE following the completion of careers intervention program based on Bandura’s four sources of information and Brown and Crane’s five critical ingredients, but goes one step further by demonstrating that such interventions can be effective in reducing CDDs.…”
Section: Discussionmentioning
confidence: 90%
“…Career education courses should be implemented early, ideally during the first or second year of high school. It would then be possible to reinforce the knowledge and skills learned across the students' entire time in high school, because a longer intervention period would reinforce and sustain the effect of the intervention (Miles & Naidoo, 2017). Schoolwide, a proactive curriculum focusing on school engagement can motivate students in career aspiration (Kenny et al, 2006; Martinez et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Students who are highly confident about their capacity in making better career decisions would have more interest to nurture their career goals, devote more time to their career explorations, and may probably make better career decisions ultimately (Gushue et al, 2006; Chiesa et al, 2016). Thus, it seems warranted to identify the antecedents of adolescents’ CDSE (Miles and Naidoo, 2017).…”
Section: Introductionmentioning
confidence: 99%